Lokasi, Kualitas Layanan dan Word of Mouth Communication terhadap Keputusan Pembelian - M. Al Kindy Dimas Ali Ghufron; Bayu Wijayantini; Wahyu Eko Setianingsih (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of location, service quality and word of mouth communication on purchasing decisions at Bumdes Mini Market Trijaya Balung Lor. This research method is descriptive quantitative. Data collection techniques using interviews and questionnaires to 100 respondents with purposive sampling technique. The results showed, a) there was a significant influence between location on purchasing decisions with a significance level of 0.000 (p <0.05); b) there is a significant influence between service quality on purchasing decisions with a significance level of 0.000 (p <0.05); c) there is a significant influence between word of mouth communication on purchasing decisions with a significance level of 0.000 (p <0.05). In conclusion, capable location, service quality, and word of mouth communication became one of the factors driving purchasing decisions at Bumdes Trijaya Balung Lor. Keywords: Purchase Decision, Service Quality, Location, Word of Mouth Communication